Damage Evolution and Circumferential Strain Distribution Characteristics of the Bolt-Supported Cavern under Multiple Explosion Sources - Taotao Wang; Ansheng Cao; Weiliang Gao; Guangyong Wang; Xiaowang Sun (Shock and Vibration)
The impact of multiple explosion sources on the safety of the underground cavern is enormous. Based on a similarity model test, the finite element software LS-DYNA3D was utilized to analyze the damage evolution and circumferential strain distribution characteristics of the bolt-supported cavern under the seven combinations of concentrated charge explosion sources in three places, including the side of the vault, side arch, and sidewall. The accuracy of the simulation results is verified by comparing them with test results. The research results indicate that the damage of the surrounding rock is mainly caused by the tensile stress wave reflected from the free surfaces and the superposition of the tensile stress wave. The damage of the surrounding rock in the cases of multiple explosion sources is not a simple superposition of that in the cases of a single explosion source. The peak circumferential stress and damage of the surrounding rock in the middle of two explosion sources are significantly greater than that of the cases of the corresponding single explosion source. In the seven cases, the peak circumferential strain of the cavern wall changes from tensile to compressive from the vault to the spandrel. When the explosion occurs on the sidewall, the peak circumferential strain of the floor is tensile.